2006
DOI: 10.1111/j.1365-2672.2006.02963.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and their fermented food products are beneficial for health

Abstract: Probiotics are usually defined as microbial food supplements with beneficial effects on the consumers. Most probiotics fall into the group of organisms’ known as lactic acid‐producing bacteria and are normally consumed in the form of yogurt, fermented milks or other fermented foods. Some of the beneficial effect of lactic acid bacteria consumption include: (i) improving intestinal tract health; (ii) enhancing the immune system, synthesizing and enhancing the bioavailability of nutrients; (iii) reducing symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
729
1
52

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,159 publications
(785 citation statements)
references
References 127 publications
3
729
1
52
Order By: Relevance
“…Probiotics is a kind of living microorganism which confers a great health benefit on the consumer when administered in adequate amounts (Parvez et al 2006). The earliest research on probiotics dates back to 1907, when Metchnikoff claimed that the people administrated lactic acid-producing bacteria in yoghurt resulting in balance of intestinal micro-flora and longevity (Metchnikoff 1987;Bron et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics is a kind of living microorganism which confers a great health benefit on the consumer when administered in adequate amounts (Parvez et al 2006). The earliest research on probiotics dates back to 1907, when Metchnikoff claimed that the people administrated lactic acid-producing bacteria in yoghurt resulting in balance of intestinal micro-flora and longevity (Metchnikoff 1987;Bron et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The important criteria which are used for selecting probiotic strains includes that the organism should be: nonpathogenic and non-toxic (Singh et al 2011); isolated from the same species as its intended host (Maurya et al 2014); able to survive during transit through the gastrointestinal tract by being acid and bile resistant (Khan and Naz 2013;Maurya et al 2014); able to adhere and colonize the intestinal epithelium which is an important property for successful immune modulation and competitive exclusion of pathogens (Kechagia et al 2013;Maurya et al 2014); able to stabilize the normal intestinal microflora (Parvez et al 2006); able to produce antimicrobial substances like the bacteriocins against the pathogens (Kral et al 2012); having a demonstrated beneficial effect on the host (Fontana et al 2013); durable enough to withstand the duress of commercial manufacturing, processing and distribution (Khan and Naz 2013); and also having good sensory characteristics by not providing unpleasant flavors or textures (Parracho et al 2007;Mitropoulou et al 2013). The essential criteria for the use of probiotics in humans has been listed in Table 2.…”
Section: Desirable Probiotic Characteristicsmentioning
confidence: 99%
“…The human gastrointestinal (GI) tract is -home‖ to a complex consortia of trillions (approximately 1 × 10 13 to 1 × 10 14 ) of microbes, thousands of bacterial phylotypes, as well as hydrogenconsuming methanogenic archaea, colonizing the entire length of the gut with a collective genome (also termed as microbiome) that contains at least 100-times as many genes as our own genome (Cho and Blaser, 2012;Wei et al, 2008). Cutting edge research and vast accumulating data indicates that the gut microbiota is instrumental in energy metabolism and immune function of the host, and has a crucial role in the development of numerous conditions including obesity (Clarke et al, 2012;Ley et al, 2006) diabetes (Bergman et al, 2006), non-alcoholic fatty liver disease (Dumas et al, 2006), inflammatory bowel diseases (Quigley, 2012;Strober et al, 2008), and cancer (Parvez et al, 2006). Mechanism of action of probiotics is not completely understood, however as general include 1) Adherence and colonization of gut, 2) Suppression of growth of pathogenic bacteria, 3) Production of antimicrobial compounds, 4) Improved intestinal barrier function, 5) Stimulation of mucosal and systemic host immunity, 6) Controlled transfer of dietary antigens (Sharma et al, 2012).…”
Section: Occurrence and Action Of Probioticsmentioning
confidence: 99%